An illustrative example of refactoring object-oriented source code with aspect-oriented mechanisms - Monteiro, Miguel Pessoa (2008)
This paper describes a refactoring process that transforms a Java source code base into a functionally equivalent AspectJ source code base. The process illustrates the use of a collection of refactorings for aspect-oriented source code, covering the extraction of scattered implementation elements to aspects, the internal reorganization of the extracted aspects and the extraction of commonalities to super-aspects.